The role of linguistics in the development of modern literary criticism: A study on linguistics and its role in the development of modern criticism methods - imirana Seydou Maiga ((الطموحات ) EL-THUMUHAT, 2019)
The nineteenth century is the age of linguistics, which opened the horizons for human sciences in this age, especially the monetary field, which is considered the first beneficiary of the fruits of linguistics, where both work on one material: language. However, linguistics was interested in the ordinary language, while the criticism in the creative language took criticism from the impressionist stage to rely on technical mechanisms to prevent the critic from falling into the trap of self-impression. And with the scientific breakthrough of criticism resulting from the exchange of criticism and linguistics we found several approaches from structural to deconstruction, stylistic, which wanted to contain the page rhetoric, and other approaches that continue to breed with the development of linguistics, and do not forget the analysis of speech, and the mechanisms of the reader and his response. These scientific observations, which will be discussed in this study in the following lines.